2019
DOI: 10.1007/s11483-019-09600-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Retrogradation Processes in Potato Starches Blended with Non-Starchy Polysaccharide Hydrocolloids by LF NMR

Abstract: Molecular dynamics for pastes of two normal and one waxy potato starches and their binary mixtures with either arabic, guar or xanthan gum was determined. Spin-lattice and spin-spin relaxation times were measured by 1H NMR pulse spectrometer. Then, for water molecules the mean correlation time rotational mobility. Was calculated and analyzed. The measurements were taken after 2 h, and then after 1, 10, 30 and 90 days of storing at 5°C. It was found that the susceptibility of pastes of potato starch to retrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This indicates that high starch concentrations reduce the passage of light through the biofilms, possibly by the formation of a more compact network of amylose and amylopectin molecules. [38,39] Differences in the TV of the biofilms could be attributed to the different size distributions of the starch granules, [40,41] the phosphate groups in starch granules, and the amylose content. [40,42] However, potato and arracacha starches exhibited a similar amylose content; therefore, the amylose content could not affect TV of the biofilms with the same starch concentration.…”
Section: Optimization Of Variables Using Response Surface Methodologymentioning
confidence: 99%
“…This indicates that high starch concentrations reduce the passage of light through the biofilms, possibly by the formation of a more compact network of amylose and amylopectin molecules. [38,39] Differences in the TV of the biofilms could be attributed to the different size distributions of the starch granules, [40,41] the phosphate groups in starch granules, and the amylose content. [40,42] However, potato and arracacha starches exhibited a similar amylose content; therefore, the amylose content could not affect TV of the biofilms with the same starch concentration.…”
Section: Optimization Of Variables Using Response Surface Methodologymentioning
confidence: 99%
“…It was also found that after 6 days of storage all tested samples were characterized by similar values of the T 21 parameter. This means that in the process of staling the bread, and in particular the process of starch retrogradation, the bound fraction molecules are immobilized (Baranowska et al, 2020;Dobosz et al, 2019;Sikora et al, 2019;Weiss et al, 2018). Measurements carried out in the bread crumb within a few hours after baking showed that the dynamics of rotation of the bulk water molecules is similar for each analyzed variant of bread (Figure 5).…”
Section: Water Activity and Water Behaviormentioning
confidence: 97%
“…In recent years, extruded flour products have also been developed world widely, and more and more foreigners like them due to the special flavour. However, after storage for a period of time, a series of problems such as loss of water, hardening of the product and poor taste will occur, which seriously influenced their quality (Baranowska, Sikora, Krystyjan, Dobosz, & Borczak, 2019).…”
Section: Introductionmentioning
confidence: 99%